Using children’s literature in ELT: A story-based approach - Pinto, Cristina Ferreira (2015)
There has been a growing interest in the role of children’s literature in language teaching since the 80s, when the communicative approach made it possible to bring stories into the classroom (Garvie, 1990). It is undeniable that storytelling has many benefits. Not only are children naturally drawn to stories, but they are also an effective and enjoyable way to teach and learn. This article presents the findings of a MA project on using stories with children. It shows the importance of stories on language acquisition and concludes with some practical suggestions based on my teaching experience with young learners.